Effect of Ginger Extrat on Anti-Botrytis Activity - ONPHACHANH, Xaykham; SALITXAY, Timnoy; CHANTHAKHOUN, Vongpasith; BRIATIA, Xoxiong; MANYSOAT, Southanou; DUANGVICHIT, Khamla (Souphanouvong University Journal Multidisciplinary Research and Development, 2020)
This reseach aimed to study the efficiency of Ginger extracts against botrytis. Ginger was extracted from 3 kinds of solvent (equa, Ethanol, Methanol). The result of this study showed the abilility to extract the 3 types of solvent. Ethanol could be extracted the highest percentage of yield 40.97±1.04% followed by equa and Methanol 27.71±1.04% and 22.16±1.04% respectively. TheThree crude extracts were investigated for their inhibitory effects against botrytis by using well diffusion test and all crude extracts were demonstrated The Minimum inhibition concentration (MIC). The sensitivity testing the Ethanol and Methanol extract showed the same strong activity against botrytis even positive control (tystatin) 1.50± 0.061cm, 1.41±0.061 cm, 1.31±0.061 cm respectively but Aqua extract was lowest 0.85±0.061cm. In minimum inhibition concentrations for botrytis found that Ethanol and Methanol extract has lowest MICs (6.25mg/ml). For Aqua Extract has lowest MICs (12.5 mg/ml). In conclusion, the extract of ginger could be considered as a good anti-botrytis agent against botrytis and Alcoholic group extraction is good solvent of Ginger extraction for against botrytis especially Ethamol.